Immediate Effects of Dasatinib on the Migration and Redistribution of Naïve and Memory Lymphocytes Associated With Lymphocytosis in Chronic Myeloid Leukemia Patients - Colom-Fernández, Beatriz; Kreutzman, Anna; Marcos-Jiménez, Ana; García-Gutiérrez, Valentín; Cuesta-Mateos, Carlos; Portero-Sainz, Itxaso; Pérez-García, Yaiza; Casado, Luis Felipe; Sánchez-Guijo, Fermín; Martínez-López, Joaquín; Ayala, Rosa M.; Boqué, Concha; et al. (Frontiers in Pharmacology, 2019)
Dasatinib is a dual SRC/ABL tyrosine kinase inhibitor that is used to treat chronic myeloid leukemia (CML) and is known to have unique immunomodulatory effects. In particular, dasatinib typically causes a lymphocytosis after intake, which has been linked to better clinical response. Since the underlying mechanisms are not known and SRC family kinase is involved in many cellular motility processes, we hypothesized that the movement and migration of lymphocytes was being modulated by dasatinib. We collected peripheral blood samples from dasatinib second-line CML patients before and after two hours from the first intake of dasatinib, and follow-up samples from the same patients 3 and 6 months after the start of therapy. The migratory capacity and phenotype of the lymphocytes and blood differential counts were compared before and after drug intake at all the study time-points. We report here for the first time that dasatinib intake is associate to an inhibition of the migration of peripheral blood T-cells towards the homeostatic chemokines CCL19 and CCL21, which controls the trafficking towards the secondary lymphoid organs, mainly the lymph nodes. Accordingly, the proportion in blood of lymphocytes expressing CCR7, the chemokine receptor for both CCL19 and CCL21, decreased after the intake including both naïve CCR7+CD45RA+ and central memory CCR7+CD45RA- T-cells. Similarly, naïve B-cells also diminished with dasatinib. Finally, such changes in the migratory patterns did not occur in those patients whose lymphocytes counts remained unchanged after taking the drug. We, therefore, conclude that lymphocytosis induced by dasatinib mirrored a pronounced redistribution of naïve and memory lymphocyte affecting all lymphocyte subsets including CD4+ and CD8+ T-cells and B-cells.